A Survey of Brazilian Patients with Oral Lichen Planus Showing No Evidence of Malignancy - Dante Migliari; Norberto Sugaya; Silvio Hirota (Hindawi Limited, 2022)
Objectives. There is conflicting evidence as to whether oral lichen planus (OLP) can undergo malignant transformation into oral squamous cell carcinoma (OSCC). This study aimed to address this issue by analyzing a sample of Brazilian patients with either OLP or OSCC. Patients and Methods. This study was conducted in São Paulo, the world's fourth-largest city by population. Two groups of patients were analyzed. The OLP group consisted of 370 patients, while the OSCC group consisted of 154 patients. The OLP patients were followed up for up to 21 years to monitor clinical benefits from the management or changes in the lesion morphology; conversely, patients with OSCC were examined only twice for diagnostic purposes and referred to a specialized center. Data concerning systemic diseases, use of medications, type of oral lesions, and health-risk behaviors were recorded for patients in both groups. Results. None of the patients with OLP developed OSCC at the lesion site. Only one female patient with erosive OLP developed OSCC in the normal, lesion-free oral mucosa. None of the OSCC patients had concomitant OLP lesions; however, a higher percentage of OSCC cases (17.5%) showed white plaques (most likely oral leukoplakia) as a precursor lesion. Conclusion. The findings strongly suggest that malignant transformation of OLP is virtually nonexistent in the Brazilian population.